An Early mtUPR: Redistribution of the Nuclear Transcription Factor Rox1 to Mitochondria Protects against Intramitochondrial Proteotoxic Aggregates - Poveda-Huertes, Daniel (Mol Cell, 2020)
The mitochondrial proteome is built mainly by import of nuclear-encoded precursors, which are targeted mostly by cleavable presequences. Presequence processing upon import is essential for proteostasis and survival, but the consequences of dysfunctional protein maturation are unknown. We find that impaired presequence processing causes accumulation of precursors inside mitochondria that form aggregates, which escape degradation and unexpectedly do not cause cell death. Instead, cells survive via activation of a mitochondrial unfolded protein response (mtUPR)-like pathway that is triggered very early after precursor accumulation. In contrast to classical stress pathways, this immediate response maintains mitochondrial protein import, membrane potential, and translation through translocation of the nuclear HMG-box transcription factor Rox1 to mitochondria. Rox1 binds mtDNA and performs a TFAM-like function pivotal for transcription and translation. Induction of early mtUPR provides a reversible stress model to mechanistically dissect the initial steps in mtUPR pathways with the stressTFAM Rox1 as the first line of defense.